Understanding the support needs of Australian nursing students during COVID-19: a cross-sectional study. Issue 3 (4th July 2021) - Alomari, Albara; Hunt, Leanne; Lord, Heidi; Halcomb, Elizabeth; Fernandez, Ritin; Middleton, Rebekkah; Moxham, Lorna
Abstract : Background : COVID-19 has caused significant disruption. This has been particularly evident within the university student population where their traditional ways of learning were abruptly reorganised and support structures removed. Objective : This paper aims to explore undergraduate student nurses' perceptions of the support required from the university during COVID-19 using the Achievement Goal Theory framework. Design : Data were collected via an online survey of undergraduate student nurses from an Australian university. This paper is reporting the data from a single open-ended item asking participants about their support needs from the University. Data were analysed using thematic analysis. Results : Of the 178 students who responded 206 individual statements were provided about the support they would like from the university. Four primary themes emerged, Support beyond academia, Academic support, Online learning readiness and Clinical practice units and clinical placement. The students identified that their needs during this pandemic include financial needs, social isolation, needs for more communication and unpreparedness for online teaching. Conclusion : Several factors were identified by participants about the additional support required from the university during COVID-19. Understanding and addressing these factors have the potential to improve student support during COVID-19 and support students in future crises. Impact statement : Understanding what support students perceive they require from the university during significant disruption will assist in future crisis management planning.